Ctenogobius boleosoma (Jordan & Gilbert, 1882) (Gobiiformes: Gobiidae), the northwesternmost record of an alien goby in the Mediterranean Sea, and a review of Mediterranean alien gobies - KOVAČIĆ , MARCELO; SACCHETTI, STEFANO (Mediterranean Marine Science, 2023)
The Western Atlantic goby Ctenogobius boleosoma (Jordan & Gilbert, 1882) was found at the Agri River mouth, south Italy. It is the northwesternmost record of an alien goby recorded in the Mediterranean Sea. The present record confirms the presence of C. boleosoma in the Mediterranean Sea, recently reported only by the DNA barcoding of larvae collected in the mesopelagic depths of the Levant Sea. The present record of adult individuals, including ripe females, indicates an established population present in shallow estuarine waters matching the species’ native habitat conditions. The morphology and coloration of Mediterranean C. boleosoma are described and discussed. A detailed description of the cephalic lateral-line system of C. boleosoma is given for the first time. Ten species of the Mediterranean alien gobies are most likely Lessepsian migrants. Three gobiid aliens are Indo-Pacific gobies not present in the Red Sea and probably introduced by shipping. The alien gobies include only one Atlantic species and the Eastern Atlantic ingression component is lacking compared to the other alien fishes in the Mediterranean Sea. Indo-Pacific gobies have been quite successful in the colonization in Mediterranean and in the establishment of the Levant populations. However, contrary to other alien fishes, gobies show limited distribution across the Mediterranean Sea, with almost all alien gobies still being restricted to the Levant.